2012
DOI: 10.1242/jeb.076794
|View full text |Cite
|
Sign up to set email alerts
|

Context-dependent correlation between resting metabolic rate and daily energy expenditure in wild chipmunks

Abstract: SUMMARYSeveral empirical studies have shown that variation in daily energy expenditure (DEE) and resting metabolic rate (RMR) is influenced by environmental and individual factors, but whether these shared influences are responsible for, or independent of, relationships between DEE and RMR remains unknown. The objectives of this study were to (i) simultaneously evaluate the effects of environmental and individual variables on DEE and RMR in free-ranging eastern chipmunks (Tamias striatus) and (ii) quantify the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 79 publications
2
29
3
Order By: Relevance
“…This is in stark contrast to many previous intra specific studies that report nonsignificant results (Meerlo et al 1997;Peterson et al 1998;Fyhn et al 2001;Speakman et al 2003). Aside from one study, based on a low sample size (n = 6, r 2 = 0.70 in Nilsson 2002), the r2 of all of the previously reported statistically significant correlations falls below the range ob served in this study: r2 = 0.20 in Tieleman et al (2008), r2 = 0.23 in Careau et al (2013), r 2 = 0.35in Vezinaetal. (2006), and r 2 = 0.50 in Rezende et al (2009).…”
Section: Dcontrasting
confidence: 94%
See 2 more Smart Citations
“…This is in stark contrast to many previous intra specific studies that report nonsignificant results (Meerlo et al 1997;Peterson et al 1998;Fyhn et al 2001;Speakman et al 2003). Aside from one study, based on a low sample size (n = 6, r 2 = 0.70 in Nilsson 2002), the r2 of all of the previously reported statistically significant correlations falls below the range ob served in this study: r2 = 0.20 in Tieleman et al (2008), r2 = 0.23 in Careau et al (2013), r 2 = 0.35in Vezinaetal. (2006), and r 2 = 0.50 in Rezende et al (2009).…”
Section: Dcontrasting
confidence: 94%
“…One noticeable difference is that our results are based on heart rate telemetry, whereas all of the studies listed above used doubly labeled water and respirometry techniques to estimate DEE and BMR. Moreover, most of the previous studies reported correlations on a mass-residual basis (Careau et al 2013 also reported statistically significant corre lations on a whole-animal basis), whereas our results are not adjusted for body mass differences between individuals. Previ ous studies investigated correlations across individuals, whereas in this study each data point is composed of the same set of animals.…”
Section: Dcontrasting
confidence: 66%
See 1 more Smart Citation
“…This is important because environmental variation is lower under laboratory-controlled conditions (Riska et al 1989), which is likely to inflate repeatability estimates (Bech et al 1999). There are only a few articles reporting long-term repeatability of BM and RMR in wild mammalian populations (Szafrań ska et al 2007;Boratyń ski and Koteja 2009;Larivée et al 2010;Careau et al 2013). Larivée et al (2010) demonstrated that long-term RMR of overwintering North American squirrels was repeatable only in females.…”
Section: Discussionmentioning
confidence: 99%
“…While this assumption is met in studies carried out under laboratory or seminatural conditions (e.g., Mauget et al 1996;Fuglei and Øritsland 1999;Arnold et al 2004Arnold et al , 2006Bozinovic et al 2004;Fuglesteg et al 2006;Kumagai et al 2006;Sparling et al 2006;Kitao et al 2009), there are practically no studies (except one; Iverson and Turner 1974) focused on that problem in the wild. There are also relatively few studies that investigate seasonal changes in RMR or BMR in wild populations (Boratyń ski and Koteja 2009;Larivée et al 2010;Careau et al 2013). Information on longitudinal consistency is essential for the proper interpretation of the variation of studied traits at the population level, the reason being that between-season changes in the population means that the traits in question can be due to (1) selective mortality/emigration of individuals characterized by a specific value of the trait, (2) a concerted shift of trait values at the individual level, which represents the expression of phenotypic plasticity in the trait expression of individuals (Gienapp et al 2008), or (3) a mix of 1 and 2.…”
Section: Introductionmentioning
confidence: 99%